Technical solutions for the transmission of electricity at high voltage in arctic conditions - Varivodov V.N.; Kovalev D.I.; Golubev D.V.; Elfimov S.A.; Zhulikov S.S. (Российская Арктика)
The article considers the main solutions to the problems that arise during the transmission of high voltage electricity in the Far North. The relevance of this topic is associated with the high strategic importance of the Arctic zone for the Russian Federation and ensuring national security for the period up to 2035. Within the framework of this strategy, it is necessary to develop and implement engineering and technical solutions for the transmission of electric power that ensure the stable functioning of the infrastructure in extreme climatic conditions. An analysis of existing solutions for the transmission of electricity in the Arctic zone was carried out. For overhead and cable power lines, their design features, their operating conditions, as well as the features of laying at extremely low temperatures are described.